Effects of Salicylic Acid on Physiological Responses of Pepper Plants Pre-Subjected to Drought under Rehydration Conditions - Gonçalves, Fabrício Custódio de Moura [UNESP]; Mantoan, Luís Paulo Benetti [UNESP]; Corrêa, Carla Verônica [UNESP]; Parreiras, Nathália de Souza [UNESP]; de Almeida, Luiz Fernando Rolim [UNESP]; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP]; Prado, Renato de Mello [UNESP]; Boaro, Carmen Sílvia Fernandes [UNESP] (MDPI, 2024)
Capsicum annuum L. has worldwide distribution, but drought has limited its production. There is a lack of research to better understand how this species copes with drought stress, whether it is reversible, and the effects of mitigating agents such as salicylic acid (SA). Therefore, this study aimed to understand the mechanisms of action of SA and rehydration on the physiology of pepper plants grown under drought conditions. The factorial scheme adopted was 3 × 4, with three water regimes (irrigation, drought, and rehydration) and four SA concentrations, namely: 0 (control), 0.5, 1, and 1.5 mM. This study evaluated leaf water percentage, water potential of shoots, chlorophylls (a and b), carotenoids, stomatal conductance, chlorophyll a fluorescence, and hydrogen peroxide (H2O2) concentration at different times of day, water conditions (irrigation, drought, and rehydration), and SA applications (without the addition of a regulator (0) and with the addition of SA at concentrations equal to 0.5, 1, and 1.5 mM). In general, exogenous SA application increased stomatal conductance (gs) responses and modified the fluorescence parameters (ΦPSII, qP, ETR, NPQ, D, and E) of sweet pepper plants subjected to drought followed by rehydration. It was found that the use of SA, especially at concentrations of 1 mM in combination with rehydration, modulates gs, which is reflected in a higher electron transport rate. This, along with the production of photosynthetic pigments, suggests that H2O2 did not cause membrane damage, thereby mitigating the water deficit in pepper plants. Plants under drought conditions and rehydration with foliar SA application at concentrations of 1 mM demonstrated protection against damage resulting from water stress. Focusing on sustainable productivity, foliar SA application of 1 mM could be recommended as a technique to overcome the adverse effects of water stress on pepper plants cultivated in arid and semi-arid regions.
Keywords: chlorophyll a fluorescence; hydrogen peroxide; photosynthetic pigments; stomatal conductance; vegetal regulator; water deficit